Effects of double and triple bonds on the spatial representations of odorants in the rat olfactory bulb - Johnson, Brett A. (2007)
Many naturally occurring volatile chemicals that are detected through the sense of smell contain unsaturated (double or triple) carbon-carbon bonds. These bonds can impact odors perceived by humans, yet in a prior study of unsaturated hydrocarbons we found only very minor effects of unsaturated bonds. In the present study, we tested the possibility that unsaturated bonds affect the recognition of oxygen-containing functional groups, because humans perceive odor differences between such molecules. We therefore compared spatial activity patterns across the entire glomerular layer of the rat olfactory bulb evoked by oxygen-containing odorants differing systematically in the presence, position, number, and stereochemistry of unsaturated bonds. We quantified activity patterns by mapping [(14)C]2-deoxyglucose uptake into anatomically standardized data matrices, which we compared statistically. We found that the presence and number of unsaturated bonds consistently affected activity patterns, with the largest effect related to the presence of a triple bond. Effects of bond saturation included a loss of activity in glomeruli strongly activated by the corresponding saturated odorants, and/or the presence of activity in areas not stimulated by the corresponding saturated compounds. The position of double bonds also affected patterns of activity, but cis versus trans configuration had no measurable impact in all five sets of stereoisomers we studied. These results simultaneously indicate the importance of interactions between carbon-carbon bond types and functional groups in the neural coding of odorant chemical information and highlight the emerging concept that the rat olfactory system is more sensitive to certain types of chemical differences than others.